HUBUNGAN FUNGSI AFEKTIF KELUARGA DENGAN KECERDASAN EMOSIONAL REMAJA DI SMA NEGERI 1 KECAMATAN PANAI HULU KABUPATEN LABUHAN BATU TAHUN 2019 - Rentawati Purba; kurnia Novita Putri Harahap (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
One of the family vital function is affective function. Fulfilling the affective function of the family is defined as the ability of the family to meet the need for comfort and happiness. Adolescents are now very worried because they experience difficulties in emotional intelligence due to the lack of family support they receive and is at risk of the teenager doing negative things or deviating. This type of research is descriptive with an approach Cross Sectional to know relationship between family affective and adolescent emotional intelligence. Location of this research was conducted at SMA Negeri 1 Sub District Panai Hulu District Labuhan Batu and this research was conducted in November 2018. The sample of this study was students on SMA Negeri 1 Sub District Panai Hulu District Labuhan Batu which numbered 86 people whose sampling uses techniques Starified Random Sampling. Data analysis using test Chi-Square. Result of statistical test say, there is a relationship between family affective and adolescent emotional intelligence in SMA Negeri 1 Sub District Panai Hulu Dixtrict Labuhan Batu. The results of the study show the importance of good family affectuive functions so that adolescent emotional intelligence can be applied in a positive form.